A tese como obra de arte na era de sua reprodutibilidade tecnica - Guimarães, Nathalia Muylaert Locks [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The objective of this thesis was to create a virtual prototype thesis, which is in accordance with the new forms of content production. The creation of this prototype, which is nothing more than the implementation of a written thesis in the form of blog, allows the University to appropriate web space, since the University has lost its role as a training institution. In an age of information overload, where ordinary users appropriated the freedom to create content filter through necessary information becomes a problem. Umberto Eco, in a text on the role of universities, compared to the mass media phenomenon, says it is "necessary to invent, and impart a new art clearance", which this prototype is to be objective. That's why we call the thesis as a work of art, for the paper, the text, the standard needed to be reinvented for possible ownership of the world wide web space. Then reinforcing the technical reproducibility of the argument, urging the reader to lead to carry out its own mediation immanent way. Thus, the parody of text Walter Benjamin The Work of Art in the Age of Mechanical Reproduction (1936), parodied as The thesis as a work of art in the age of technical reproducibility; critical, not discursive form, the norms of abnt, combining the problem of quantity instead of quality to their way of exposure and data compilation. In this sense, the footnote, citation, among other standards abnt are thought in a virtual dimension. Number of pages become unnecessary when you can install a tool search. Thus, this study presents the following manner: 1) Thesis Virtual and Critique of abnt: Where has the methodology that was presented by version 1.02 (printed version, and transmedia, moving between the role of information and virtual content via QR-codes). Followed, the presentation of the virtual prototype (version 2.0) finalized on defense on June 9, 2016. And the preparation of the thesis manual work written accordly the rules of ABNT (version 2.1) to deposit in the library of the University. 2) Own content production: Where to apply the methodology of the thesis as work in the production of innovative content developed here as Critical Theory of Racket considering as the basis of development, the Free Software ideological conception (creative commons and copyleft) and Critical to the Critical Theory and the Traditional Theory by Frankfurt School.

O Objetivo dessa tese foi a de criar um protótipo de tese virtual, que esteja de acordo com as novas formas de produção de conteúdo. A criação desse protótipo, que nada mais é do que a transposição de uma tese escrita para a forma de blog permite que a Universidade se aproprie do espaço Web, uma vez que a Universidade tem perdido o seu papel enquanto instituição de formação. Em uma época de excesso de informação, onde usuários comuns se apropriam da liberdade de criar conteúdo, filtrar informação necessária se torna um problema. Humberto Eco, em um texto sobre o papel das universidades, frente ao fenômeno do mídia mass, diz que é “preciso inventar, e difundir, uma nova arte da depuração”, o que esse protótipo se objetiva a ser. É por isso, que chamamos a tese como obra de arte, pois o papel, o texto, a norma precisou ser reinventada para seja possível a apropriação do espaço da world wide web. Em seguida, reforço o argumento da reprodutibilidade técnica, incitando o leitor a conduzir a realizar sua própria mediação de maneira imanente. Desse modo, a paródia do texto de Walter Benjamim A obra de arte na era de sua reprodutibilidade técnica, parodiado como: A tese como obra de arte na era de sua reprodutibilidade técnica; crítica, de forma não discursiva, as normas da abnt, aliando o problema da quantidade no lugar de qualidade a sua forma de exposição e compilação de dados. Nesse sentido, a nota de rodapé, a citação, entre outras normas da abnt são pensadas em uma dimensão virtual. Número de páginas se tornam desnecessários, quando é possível instalar uma ferramenta (plugin1) de busca. Desse modo, a presente pesquisa se apresenta da seguinte forma: 1) Tese Virtual e Crítica a abnt: Onde apresenta-se a metodologia que foi apresentada pela versão 1.02 (Versão impressa, e transmidiática, transitando entre a informação do papel e os conteúdos virtuais através de QR-codes, entregue a banca) Seguido, da apresentação do protótipo virtual (versão 2.0) finalizado, no dia da defesa em 9 de junho de 2016. E da elaboração do manual da tese como obra nas normas da abnt (versão 2.1) para depósito na biblioteca da Universidade. 2) Produção de conteúdo próprio: Onde se aplica a metodologia da tese como obra na produção de conteúdo inovador, desenvolvido aqui como Teoria Crítica do Racket considerando como base de desenvolvimento, a concepção ideológica de Software Livre (creative commons e copyleft ) e a Crítica a Teoria Crítica e a Teoria Tradicional
The thesis as work of art in the age of mechanical reprodution
Keywords: Virtual thesis; Paradigmatic revolution; ABNT critical; Critical theory of Racket; Hackativism; Free software; Tese virtual; Crítica ABNT; Revolução paradigmática; Software livre; Hackativismo